. Predictive value of Serum tumor markers (carcinoembryonic antigen , neuron-specific enolase , and squamous cell carcinoma antigen in Non-small Cell Lung Cancer Patients Treated with Programmed Cell Death Protein 1 Inhibitors : Predictive Study of Serum tumor markers in PD-1 Inhibitors in NSCLC - Wang, Yang (Journal of Medical Biochemistry, 2025)
Introduction: in patients with advanced non-small cell lung cancer (ANSCLC) undergoing treatment with programmed cell death protein 1 (PD-1) inhibitors (PD-1Is), adverse reactions (ARs) may occur. Establishing a risk assessment model can facilitate personalized treatment. Materials and Methods: clinical data were collected from 215 ANSCLC patients treated with PD-1Is. Patients who experienced ARs were classified as the observation group (OG, 92 cases), while those who did not experience ARs were classified as the control group (CG, 123 cases). A multivariable logistic regression (LR) model was employed to analyze independent risk factors (RFs) associated with ARs, and R Studio software was utilized to create a nomogram predictive model. Results:the concordance index for the nomogram predictive model for ARs in ANSCLC patients treated with PD-1Is was 0.911. The threshold for predicting ARs using the nomogram was greater than 0.25, providing a clinical net benefit superior to individual indicators such as smoking, tumor-node-metastasis (TNM) staging, neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), and prognostic nutritional index (PNI). The proportion of smokers in the OG was markedly superior to that in the CG (P
Keywords: carcinoembryonic antigen , neuron-specific enolase , and squamous cell carcinoma antigen ,non-small cell lung cancer; PD-1 inhibitors; adverse reactions; nomogram predictive model; multivariable logistic regression model.